Molecular study of the giardia parasite in the beauty of the province of Diwaniyah (Eurasian Journal of Research, Development and Innovation, 2024)
Because of little studies which related with camels in Iraq, our study aimed to description of Giardia lamblia in it, in parasitology laboratory of Life Sciences in Qadissiya University.The current study included a random examination of 100 fecal samples of camels from slaughterhouses and Bedouin areas in Diwaniyah Governorate. Some camels suffered from diarrhea and other asymptomatic animals from October 2019 to the end of April 2020, and their ages ranged from random examination. The infection with giardiasis (40 samples, 20%) was by direct smear, flotation method, and by using light microscopy to detect parasite phases and cysts. The incidence of giardia parasites was 19.3%.The prevalence rate according to the age of the camel, Giardia infection was higher at age less than 44.4%, while the rate decreased at age more than 17.5%. According to the most popular study of giardia infection, the highest range is 28.1% in January and the lowest range is 3.3% in December. Statistical analysis of results showed there is significant difference in both parasite infections among the age range and months of study.Regarding the prevalence of parasites, 100 faecal samples were examined using polymerase chain reaction (PCR) technique. The prevalence of giardia (39%) in Diwaniyah.This study showed that camels are the source of infection with the studied parasites, which are considered parasites of animal origin.